The gender gap in political psychology - Lönnqvist, Jan-Erik (Frontiers in Psychology, 2022)
Introduction I investigated the authorship gender gap in research on political psychology. Methods The material comprises 1,166 articles published in the field’s flagship journal Political Psychology between 1997 and 2021. These were rated for author gender, methodology, purpose, and topic. Results Women were underrepresented as authors (37.1% women), single authors (33.5% women), and lead authors (35.1% women). There were disproportionately many women lead authors in papers employing interviews or qualitative methodology, and in research with an applied purpose (these were all less cited). In contrast, men were overrepresented as authors of papers employing quantitative methods. Regarding topics, women were overrepresented as authors on Gender, Identity, Culture and Language, and Religion, and men were overrepresented as authors on Neuroscience and Evolutionary Psychology. Discussion The (denigrated) methods, purposes, and topics of women doing research on politics correspond to the (denigrated) “feminine style” of women doing politics grounding knowledge in the concrete, lived reality of others; listening and giving voice to marginalized groups’ subjective experiences; and yielding power to get things done for others.